2020
DOI: 10.1186/s13053-020-00148-9
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of outcomes in patients with DNA-damage repair related pancreatic cancer

Abstract: Background: Patients with DNA-damage response genes (DDR)-related pancreas cancer (BRCA1/2 or other DNAdamage related genes) may have improved outcomes secondary to increased sensitivity to DNA-damaging drugs (platinum chemotherapy/ poly ADP ribose polymerase (PARP)-inhibitors). However, data is scarce pertaining to outcomes in this subset of patients. Our objective was to retrospectively identify DDR-related pancreas cancer patients and report on clinical outcomes. Methods: Pancreas cancer patients with a ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This was recently shown in a retrospective study of 262 patients with PDAC in which 19% of the patients were found to have HRm (defined as germline or somatic pathogenic alterations of 17 HRm including ATM , BRCA1 , and BRCA2 ); PFS was better in patients with HRm when platinum‐based therapy was used compared with nonplatinum‐based therapy [6]. Additional series are corroborating better outcomes in patients harboring the HRm aberrations, highlighting the value of identifiyin these patients [42]. In our study, we detected HRm in 8.8% of the patients.…”
Section: Discussionmentioning
confidence: 96%
“…This was recently shown in a retrospective study of 262 patients with PDAC in which 19% of the patients were found to have HRm (defined as germline or somatic pathogenic alterations of 17 HRm including ATM , BRCA1 , and BRCA2 ); PFS was better in patients with HRm when platinum‐based therapy was used compared with nonplatinum‐based therapy [6]. Additional series are corroborating better outcomes in patients harboring the HRm aberrations, highlighting the value of identifiyin these patients [42]. In our study, we detected HRm in 8.8% of the patients.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, while PGVs in certain DNA damage repair genes (e.g. BRIP1 , CHEK2 , FANCC , NBN , RAD50 , RAD51C , RAD51D ) are not currently linked to PDAC risk or included in PDAC surveillance guidelines, there is considerable interest in defining their role in PDAC tumorigenesis and treatment response 8,37,38 . As broader multi‐gene panels become more common, documenting all findings in pancreatic cancer families through registries will be important to advancing understanding of the missing heritability for pancreatic cancer, and also offers opportunities to provide couseling for other cancer risks.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pancreatic cancers, recent studies reported that germline mutations in genes such as BRCA1, BRCA2, PALB2, and CDKN2A occur in about 10-20% of patients without extra-pancreatic manifestations, and 5-8% of patients with pancreatic cancer without family history are in fact carriers of germline mutations [34,35]. Some studies have reported a near doubling of the risk of pancreatic cancer in BRCA female carriers [36].…”
Section: Predisposition To Pancreatic Cancer With Brca and Associated...mentioning
confidence: 99%